Kadar Polifenol dan Aktivitas Antioksidan Yoghurt Teh dengan Inokulum Caspian Sea selama fermentasi - Maharani, Shinta; Sugiarti, Yatti; Al Falah, Sarah Amelia Nur Wahidah; Prawira-Atmaja, M Iqbal (Program Studi Teknologi Pangan, 2021)
Tea is a beverage containing bioactive compounds with beneficial health benefits. This study aims to determine total polyphenols and antioxidant activity changes of yoghurt enriched with black and green tea infusion during fermentation. Observation was carried out on the fermentation 0, 4, 8, and 12 hours. The results showed that total polyphenol and antioxidant activity of yoghurt enriched with black and green tea infusion is higher than plain yoghurt (control). During fermentation, total polyphennol increased significantly from 36.42 mg GAE/g and 36.91 mg GAE/g at 0 hour fermentation to 106 mg GAE/g and 107 mg GAE/g at 12 hours fermentation on yoghurt enriched with black and green tea infusion, respectively. Yoghurt enriched with black and green tea infusion had the highest DPPH scavenging activity when compared to yoghurt control at the end of fermentation (12 hours) i.e.96.87%; 95.56%; and 18.98%, respectively. Based these findings, yoghurt enriched with black and green tea infusion can be applied to improve total polyphenol and antioxidant activities at the end of fermentation (12 hours).Â